2019
DOI: 10.22146/ijccs.48203
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rice Variety Using Geometric Features and Neural Network

Abstract: Indonesia has many food varieties, one of which is rice varieties. Each rice variety has physical characteristics that can be recognized through color, texture, and shape. Based on these physical characteristics, rice can be identified using the Neural Network. Research using 12 features has not optimal results. This study proposes the addition of geometry features with Learning Vector Quantization and Backpropagation algorithms that are used separately.The trial uses data from 9 rice varieties taken from seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In 2019, Srimulyani et al conducted a comparative study which observed that a rice identification system using BPNN outperformed LVQ based approach [57]. In the preprocessing phase, the image segmentation using thresholding and contour tracking was performed.…”
Section: ) Unsupervised Learningmentioning
confidence: 99%
“…In 2019, Srimulyani et al conducted a comparative study which observed that a rice identification system using BPNN outperformed LVQ based approach [57]. In the preprocessing phase, the image segmentation using thresholding and contour tracking was performed.…”
Section: ) Unsupervised Learningmentioning
confidence: 99%
“…Rice has diferent types. C4Raja rice [12], and kernel rice features depend on length, width, and perimeters [13]. Several rice types, such as Chenab Basmati, Kissan Basmati, Basmati 2000, KSK 133, KSK 434, Punjab Basmati, and PK 1121 aromatic, are mostly grown in Pakistan, are utilized for rice seed categorization, and have been gathered [14].…”
Section: Introductionmentioning
confidence: 99%